Population structure of lake whitefish (Coregonus clupeaformis) from the Mississippian lineage in North America - Carly F. Graham; Douglas R. Boreham; Richard G. Manzon; Joanna Y. Wilson; Christopher M. Somers (Canadian Science Publishing, 2022)
The lake whitefish (Coregonus clupeaformis) is a commercially valuable freshwater species with a broad distribution in North America. Some phylogeographic work has been done on this species, but little is known about genetic population subdivision among populations of the widely dispersed Mississippian lineage. We used 3,173 single nucleotide polymorphisms in 508 lake whitefish from 22 different lakes to examine population structure across central Canada and the United States. Bayesian clustering, ordination, and fixation indices identified population subdivision that largely reflected geographic distance and hydrological connectivity, with greater differentiation between lakes that are farther apart. Population subdivision was hierarchical, with greater differentiation between Canadian provinces and less differentiation based on river basins within provincial boundaries. Interestingly, isolation by distance alone was not sufficient to account for all of the observed genetic differentiation among populations. We conclude that important components of lake whitefish genetic diversity are present at different spatial scales, and that populations within the Mississippian lineage have differentiated widely across their range.